Giraffes can't dance - Andreae, Giles, 1966-; Parker-Rees, Guy (New York : Orchard Books, 2001)
Gerald the giraffe is too clumsy to dance with all the other animals at the Jungle Dance, until he finds the right music.
Publisher's Weekly
4.3
K-3.
K-3
Keywords: Dance -- Juvenile fiction; Giraffe -- Juvenile fiction; Individuality -- Juvenile fiction; Dance -- Fiction; Giraffe -- Fiction; Individuality -- Fiction; Stories in rhyme; Dance -- Fiction; Giraffes -- Fiction; Individuality -- Fiction; Stories in rhyme